Heroínas atuais e o desenvolvimento feminino - Conde, Marina Marques (2023)
This work results from qualitative research aiming to analyze the female psychological development represented in the path of the heroines in the movies Moana (2016) and Raya and the Last Dragon (2021) through the approach of Analytical Psychology. The analysis considered as an object of study only the protagonist princesses of each film and was based on the method of interpretation of fairy tales described by Von Franz (1999/2007). After deciphering the trajectory of each character, the results were analyzed symbolically. It was concluded that there was a transformation in the representation of the female image. The heroines portray a new female model that corroborates the bibliography elaborated in the theoretical development of this paper. Moana and Raya represent strong, independent, and strategic women who do not submit to male characters. Thus, a female model that impacts new generations and contributes to the women's movement toward equality is built